Complexity of Maker–Breaker games on edge sets of graphs - Duchêne, Eric; Gledel, Valentin; Mc Inerney, Fionn; Nisse, Nicolas; Oijid, Nacim; Parreau, Aline; Stojaković, Miloš (Discrete Applied Mathematics, 2025)
We study the algorithmic complexity of Maker–Breaker games played on the edge sets of general graphs. We mainly consider the perfect matching game and the H-game. Maker wins if she claims the edges of a perfect matching in the first, and a copy of a fixed graph H in the second. We prove that deciding who wins the perfect matching game and the H-game is PSPACE-complete, even for the latter in small-diameter graphs if H is a tree. Toward finding the smallest graph H for which the H-game is PSPACE-complete, we also prove that such an H of order 51 and size 57 exists. We then give several positive results for the H-game. As the H-game is already PSPACE-complete when H is a tree, we mainly consider the case where H belongs to a subclass of trees. In particular, we design two linear-time algorithms, both based on structural characterizations, to decide the winners of the P4-game in general graphs and the K1,ℓ-game in trees. Then, we prove that the K1,ℓ-game in any graph, and the H-game in trees are both FPT parameterized by the length of the game, notably adding to the short list of games with this property, which is of independent interest. Another natural direction to take is to consider the H-game when H is a cycle. While we were unable to resolve this case, we prove that the related arboricity-k game is polynomial-time solvable. In particular, when k=2, Maker wins this game if she claims the edges of any cycle.